Internalisasi Nilai Moderat Dalam Membangun Kerukunan Masyarakat Lamongan - Moch Faizin Muflich; Binti Nurhayati (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The diversity of society tends to be a burden rather than a source of strength for the Indonesian state in the current reform era. The current state of people's tastes and attitudes is a setback from what has happened in the past. The lack of commitment to use tolerance as a strategy to overcome various issues that contribute to the country's decline leads to intolerance. This is contrary to what the peaceful residents of Balun Turi Lamongan do. The religious community in this village which consists of Muslims, Hindus, and Christians shows the unique approach of the Balun people in respecting diversity and tolerance by living side by side peacefully and participating in interfaith celebrations. This does not escape the process of internalizing or inculcating moderate values ​​that are carried out in the village of Balun through three phases, namely, the value transformation phase, value transaction, and value transinternalization so that the moderate value produced is in the form of tasamuh value, shura value, i' tidal value. value, the value of musawah, and the value of wataniyah and muwatanah.